Sulfur doped graphene/polystyrene nanocomposites for electromagnetic interference shielding - Shahzad, Faisal; Yu, Seunggun; Kumar, Pradip; Lee, Jang-Woo; Kim, Yoon-Hyun; Hong, Soon Man; Koo, Chong Min (ELSEVIER SCI LTD, 2015)
In this paper, for the first time, we present a simple and straightforward method to improve not only electrical conductivity and complex permittivity but also electromagnetic interference (EMI) shielding effectiveness of reduced graphene oxide (rGO)/polystyrene (PS) nanocomposites through sulfur doping. Sulfur-doped reduced graphene oxide with thiophene-like structure (2.6 at.% S), synthesized through a simple heating process of a mixture of graphene oxide and sulfur powder, revealed almost three times larger electrical conductivity (1095 S m(-1)) than undoped rGO (395 S m(-1)). The SrGO/PS nanocomposite showed not only 150% larger electrical conductivity and 50% larger complex permittivity, but also improved EMI shielding effectiveness (24.5 dB) at a frequency of 18 GHz than rGO/PS nanocomposite (21.4 dB) at the same loading level of 7.5 vol.%. Considering the simplicity and effectiveness of process, sulfur doping of graphene is expected to be used as a versatile method to improve EMI shielding efficiency of graphene/polymer nanocomposites. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: REDUCED GRAPHENE OXIDE; CARBON NANOTUBE COMPOSITES; WAVE ABSORPTION PROPERTIES; OXYGEN REDUCTION REACTIONS; HIGHLY EFFICIENT; ELECTRICAL-CONDUCTIVITY; CHEMICAL-REDUCTION; THIN-FILMS; TRANSPARENT; LIGHTWEIGHT